SH2 domains: modulators of nonreceptor tyrosine kinase activity. - Filippakopoulos, P; Müller, S; Knapp, S (2009)
The Src homology 2 (SH2) domain is a sequence-specific phosphotyrosine-binding module present in many signaling molecules. In cytoplasmic tyrosine kinases, the SH2 domain is located N-terminally to the catalytic kinase domain (SH1) where it mediates cellular localization, substrate recruitment, and regulation of kinase activity. Initially, structural studies established a role of the SH2 domain stabilizing the inactive state of Src family members. However, biochemical characterization showed that the presence of the SH2 domain is frequently required for catalytic activity, suggesting a crucial function stabilizing the active state of many nonreceptor tyrosine kinases. Recently, the structure of the SH2-kinase domain of Fes revealed that the SH2 domain stabilizes the active kinase conformation by direct interactions with the regulatory helix alphaC. Stabilizing interactions between the SH2 and the kinase domains have also been observed in the structures of active Csk and Abl. Interestingly, mutations in the SH2 domain found in human disease can be explained by SH2 domain destabilization or incorrect positioning of the SH2. Here we summarize our understanding of mechanisms that lead to tyrosine kinase activation by direct interactions mediated by the SH2 domain and discuss how mutations in the SH2 domain trigger kinase inactivation.